Impairment of assets and market reaction during COVID-19 pandemic on the example of WSE - Bartłomiej Lisicki (Risks, 2021)
The main task of the article is to examine the impact of the reported impairment of assets (IoA) on the market reaction of investors on the Warsaw Stock Exchange [WSE] in the crisis condition caused by the COVID-19 pandemic. There is a need to verify whether the disclosure of this information in the period of economic downturn will cause a similar negative reaction as in previous topics in this area. Research undertaken in this article helps identify the rules of behaviour (in the short term) whether the reaction of investors on updating the company's assets in crisis conditions is different than in times of prosperity. The main hypothesis will be verified using the event study methodology. It allows to verify whether the upcoming information about IoA during the COVID-19 pandemic confirms an existence of statistically significant negative abnormal returns. Based on the 55 cases of current reports informing about IoA, which were submitted to the investors in the year 2020 and finally qualified for the research sample, I have not observed statistically significant negative abnormal returns on the adjacent days. The results are different from those obtained by researchers who study the market reaction to the IoA under non-crisis conditions of the economy.
Keywords: 330; capital markets; accounting; financial reporting; economic crisis; COVID-19; shares; impairment of assets; write-off; event study; market reaction